FAKTOR RESIKO YANG BERHUBUNGAN DENGAN TERJADINYA ULKUS DIABETIK PADA PENDERITA DIABETES MELITUS TIPE 2 DI RSUD SYEKH YUSUF KABUPATEN GOWA - Saenab Dasong; Suhartatik Suhartatik; Arlin Afrianti (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
Diabetic Ulcers was a threat to people with Diabetes Mellitus and even caused amputations. The purpose of this study was to determine the relationship between risk factors and the occurrence of Diabetes Ulcers to the patients with type 2 Diabetes Mellitus at Syekh Hospital of Gowa Regency. This study was an Analytical Survey Study that the researcher conducted a cross sectional study conducted in April to May 2019. The population in this study was Type 2 of DM patients seeking treatment at Syekh Yusuf Hospital Gowa Regency, consisted 30 respondents. The results showed that age, duration of DM and adherence to take medication had a significant relationship with the occurrence of Diabetes Ulcers in type 2 of DM patients. All factors had a value <0.05. It was expected that patients will always increase efforts to prevent the occurrence of Diabetic Ulcers through the prevention of various risk factors for Diabetic Ulcers in patients with type 2 Diabetes. So, this needed to be considered by health workers to pay attention to the risk factors. One of the factors that could be modified was medication adherence because it affected the patient's blood sugar levels that had impacted on the complications of Diabetic Ulcers.Keywords: Age, Length of Suffering from Diabetes Mellitus, Compliance with Taking Medication, Diabetic Ulcer